Livestock Health and Farming - Abubakar, Muhammad (IntechOpen, 2020)
Livestock Health and Farming provides a detailed description of key aspects of livestock health issues and farming practices. Chapters cover such topics as antimicrobial resistance in livestock, nutrition and its role in animal health and farming, nutrition and health management in dairy animals, and livestock feeding in semi-arid regions.